Civil engineering fluid mechanics problem and solutions - Amat Sairin Demun (Penerbit UTM Press, 2017)
This book presents ten selected chapters of core topics in civil engineering fluid mechanics programmes in most universities worldwide. Each chapter consists of a list of learning outcomes, short discussion of theoretical concepts of selected topics. This is follwed by fully solved problems with step-by-step explanations of key topics.